STUDENT'S PERCEPTION ON THE CHALLENGING PROCESS OF WRITING POEM IN CREATIVE WRITING CLASS AT ENGLISH EDUCATION STUDY PROGRAM - Oktavia, Soraya; Lekatompessy, Jenny; Bilmona, Hanafi (Pattimura Excellence Journal of Language and Culture, 2024)
The objective of this research is to know student’s perception on the challenging process of writing poem in creative writing class. This research uses descriptive qualitative research approach with a case study method. The research was conducted in the fourth semester students of English education study program, Pattimura University. The sample of this research was 65 students. The instruments used for collecting the data were classroom observations, questionnaire and interview. The result of this study shows that most of the fourth semester students class B in academic year 2022/2023 in creative writing class of English Education Study Program, Pattimura University have challenges in writing poem. There are three types of challenges that the students faced during writing poem namely vocabulary, figurative language and grammatical problem. To overcome those challenges the students employed strategies namely, using dictionary, using internet, and translating. These findings suggest that it is important for the lecturer to know about the challenges that the students faced during writing poem and what the strategies their employed to overcome the challenges, in it to improve the process of writing poem so that it is better.